An Overview, Origins, Uses, and Difficulties of IoT (International Journal of Innovative Research in Computer Science & Technology, 2021)
The Internet of Things (IoT) is quickly  expanding nowadays. In the near future, billions of  gadgets are likely to be linked. Smart and sensing devices  have had an influence on Big Data by generating and  collecting large amounts of data during the communiqué between new physical objects. The requirement of  handling large amounts of data that might serve diverse  objectives in many sectors such as medicinal, social,  marketable, manufacturing, and methodical fields is one  of the obstacles in this communication process. The goal  of this research is to showcase some of the most current  advancements in IoT. The research was separated into  three sections: a brief history, the Big Data (BD) idea,  IoT resources (devices and programs), and lastly, few obstacles and impending prospects. The presented study's  goal is mainly to provide researchers with an up-to-date  explanation of the Internet of Things and its influence on  BD.
Keywords: Big Data; Internet of Things; IoT; IoT applications; Smart devices